2020
DOI: 10.1371/journal.pone.0235496
|View full text |Cite
|
Sign up to set email alerts
|

Association between purchasing behaviors and cigar use: A longitudinal analysis of Waves 1-3 of the Population Assessment of Tobacco and Health (PATH) Study

Abstract: Introduction Over 120 US jurisdictions have implemented policies mandating minimum cigar pack quantities, yet little empirical research exists on the relationship between pack quantity and use. We examined whether cigar use was associated with purchasing cigars by the box/pack or as singles, purchase quantity, and price paid per cigar. Methods Data are from Waves 1-3 (2013-2016) of the Population Assessment of Tobacco and Health (PATH) Study, analyzed in 2019. The sample included adults who reported current us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…These findings were consistent across two different definitions of smaller pack size; (1) singles and (2) singles and two to three packs. These findings align with King et al, who found in their longitudinal analysis of PATH data that larger pack size (box or pack vs. singles) was associated with smoking more cigarillos per day [15]. Similarly, in their review of previously secret tobacco industry documents aimed at examining how tobacco companies have used package quantity to target consumers, Persoskie et al found that larger tobacco pack sizes were designed for heavier users, while smaller pack sizes were designed for newer and lighter users [22].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings were consistent across two different definitions of smaller pack size; (1) singles and (2) singles and two to three packs. These findings align with King et al, who found in their longitudinal analysis of PATH data that larger pack size (box or pack vs. singles) was associated with smoking more cigarillos per day [15]. Similarly, in their review of previously secret tobacco industry documents aimed at examining how tobacco companies have used package quantity to target consumers, Persoskie et al found that larger tobacco pack sizes were designed for heavier users, while smaller pack sizes were designed for newer and lighter users [22].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, while larger pack sizes are more expensive overall, they are cheaper per stick and consequently may have better value for more frequent and established smokers [ 15 , 16 ]. Indeed, we found that users of larger pack sizes consumed more cigars per day and were more likely to smoke within 30 min of waking; therefore, larger pack sizes may be more economical for their consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations